Teaching and Learning Guide for "The Unbelieved and Historians, Parts I and II". Issue 4 (4th April 2017) - Clossey, Luke; Jackson, Kyle
Abstract: This teaching and learning guide accompanies the series of "The Unbelieved and Historians" articles, which argues that we should approach religious history with open minds. This guide offers related resources, readings, and a project designed for classroom use.